The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.bmc.2014.04.030
|View full text |Cite
|
Sign up to set email alerts
|

Exploring structural motifs necessary for substrate binding in the active site of Escherichia coli pantothenate kinase

Abstract: The coenzyme A (CoA) biosynthetic enzymes have been used to produce various CoA analogues, including mechanistic probes of CoA-dependent enzymes such as those involved in fatty acid biosynthesis. These enzymes are also important for the activation of the pantothenamide class of antibacterial agents, and of a recently reported family of antibiotic resistance inhibitors. Herein we report a study on the selectivity of pantothenate kinase, the first and rate limiting step of CoA biosynthesis. A robust synthetic ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 36 publications
1
14
0
Order By: Relevance
“…In order to confirm the optimal positioning of the amide-mimicking triazole group, a compound in which the triazole ring of compound 1e is shifted two carbon atoms down the chain was designed (Table 1, compound 2). It was synthesized as previously reported (25). As expected, the antiplasmodial activity of compound 2 against asexual, blood-stage P. falciparum was significantly less than that of compound 1e, with an IC 50 of 3.5 Ϯ 1.2 M (n ϭ 3; CI ϭ 2.0 to 4.9 M, power ϭ 0.998).…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…In order to confirm the optimal positioning of the amide-mimicking triazole group, a compound in which the triazole ring of compound 1e is shifted two carbon atoms down the chain was designed (Table 1, compound 2). It was synthesized as previously reported (25). As expected, the antiplasmodial activity of compound 2 against asexual, blood-stage P. falciparum was significantly less than that of compound 1e, with an IC 50 of 3.5 Ϯ 1.2 M (n ϭ 3; CI ϭ 2.0 to 4.9 M, power ϭ 0.998).…”
Section: Resultsmentioning
confidence: 69%
“…2A, Table 1), previously reported as part of an investigation into the structural requirements for substrate binding to the Escherichia coli PanK (25), was identified as a more-stable derivative of N5-Pan. Based on the description of how the triazole may mimic amide bonds by Genazzani and coworkers, a closer mimic of N5-Pan would have had its triazole moiety one carbon further away from the pantoyl group than does compound 1e; however, docking studies with selected CoA-binding enzymes suggest that compound 1e might be a better mimic of N5-Pan (note that three-dimensional [3D] structures have not been reported for any of the P. falciparum CoA biosynthesis enzymes).…”
Section: Resultsmentioning
confidence: 97%
“…The pantothenate analogues CJ-15,801 [ 25 ], N5-trz-C1-Pan [ 26 ] and N -PE-αMe-PanAm [ 21 ], used in this study were synthesised as reported previously.…”
Section: Methodsmentioning
confidence: 99%
“…Compounds containing guanidine hydrochloride (compounds 11a ~ c ) can be synthesised by the following methods. 9a ~ 9b were prepared from the appropriate aliphatic diamine [34] (Scheme S2). Hereafter, these molecules were reacted with 1a ~ b to produce 10a ~ c .…”
Section: Resultsmentioning
confidence: 99%